Classical Conditioning as a Distinct Mechanism of Placebo Effects - Bąbel, Przemysław (Frontiers in Psychiatry, 2019)
Classical conditioning was suggested as a mechanism of placebo effects in the 1950s. It was then challenged by response expectancy theory, which proposed that classical conditioning is just one of the means by which expectancies are acquired and changed. According to that account, placebo effects induced by classical conditioning are mediated by expectancies. However, in most of the previous studies, either expectancies were not measured or classical conditioning was combined with verbal suggestions. Thus, on the basis of those studies, it is not possible to conclude whether expectancies are involved in placebo effects induced by pure classical conditioning. Two lines of recent studies have challenged the idea that placebo effects induced by classical conditioning are always mediated by expectancies. First, some recent studies have shown that a hidden conditioning procedure elicits both placebo analgesia and nocebo hyperalgesia, neither of which is predicted by expectancy. Second, there are studies showing that visual cues paired with pain stimuli of high or low intensity induce both placebo analgesia and nocebo hyperalgesia when they are presented subliminally without participants’ awareness. The results of both lines of studies suggest that expectancy may not always be involved in placebo effects induced by classical conditioning and that conditioning may be a distinct mechanism of placebo effects. Thus, these results support the idea that placebo effects can be learned by classical conditioning either consciously or unconsciously. However, the existing body of evidence is limited to classically conditioned placebo effects in pain, that is, placebo analgesia and nocebo hyperalgesia.